Sustainable automotive technologies 2011 proceedings of the 3rd international conference - International Conference on Sustainable Automotive Technologies Greenville, South Carolina) 2011; Hung, Steve H.; Subic, Aleksandar; Wellnitz, Jörg (Berlin, Heidelberg Springer, 2011)
These proceedings capture papers presented at the third International Conferences on Sustainable Automotive Technologies (ICSAT), held at the Clemson University International Center for Automotive Research (CU-ICAR), Greenville, South Carolina, USA, during 5-6 April 2011. ICSAT is the state-of-the-art conference in the field of new technologies for transportation. The book summarizes all important trends in sustainability of automotive development today with a special focus on materials, propulsion technologies as well as manufacturing issues. It provides a brief selection of papers and key-note speakers of the conference. Papers from the US, Australia, Europe and Asia are showing the lighthouse character of the conference, in a field which gains more and more importance as far as emissions and the lack of fossil fuels in the future are concerned. The book provides a very good overview of R&D activities at OEMs as well as in leading universities and laboratories; the special focus is on new ideas for sustainable mobili
Preface.- Evaluating Sustainability -- Technologies for Production.-  Combustion Engines and Fuels -- Hydrogen and Electric Vehicle Technologies.- Materials and Structures -- Vehicle Syste
Electronic reproduction.
Keywords: Automobiles -- Design and construction -- Congress; Sustainable engineering -- Congresses